Use of 25-hydroxyvitamin D3 in diets for sows: A review - Lianhua Zhang; Xiangshu Piao (Animal Nutrition, 2021)
Dietary supplementation with 25-hydroxyvitamin D3 (25OHD3), as an alternative source of vitamin D, is becoming increasingly popular due to its commercialization and more efficient absorbability. The addition of 25OHD3 rather than its precursor vitamin D3 can circumvent the 25-hydroxylation reaction in the liver, indicating that supplementation of 25OHD3 can rapidly improve the circulating vitamin D status of animals. Emerging experiments have reported that maternal 25OHD3 supplementation could increase sow performances and birth outcomes and promote circulating vitamin D status of sows and their offspring. Increased milk fat content was observed in many experiments; however, others demonstrated that adding 25OHD3 to lactating sow diets increased the contents of milk protein and lactose. Although an inconsistency between the results of different experiments exists, these studies suggested that maternal 25OHD3 supplementation could alter milk composition via its effects on the mammary gland. Previous studies have demonstrated that adding 25OHD3 to sow diets could improve the mRNA expressions of insulin-induced gene 1 (INSIG1) and sterol regulatory element-binding protein 1 (SREBP1) in the mammary gland cells from milk and increase the mRNA expressions of acetyl-CoA carboxylase α (ACCα) and fatty acid synthase (FAS) in the mammary gland tissue. Maternal 25OHD3 supplementation promotes skeletal muscle development of piglets before and after parturition, and improves bone properties including bone density and bone breaking force in lactating sows and their piglets. Interestingly, 25OHD3 supplementation in sow diets could improve neonatal bone development via regulation of milk fatty acid composition related to bone metabolism and mineralization. In this review, we also discuss the effects of adding 25OHD3 to sow diets on the gut bacterial metabolites of suckling piglets, and propose that butyrate production may be associated with bone health. Therefore, to better understand the nutritional functions of maternal 25OHD3 supplementation, this paper reviews advances in the studies of 25OHD3 for sow nutrition and provides references for practical application.